2010
DOI: 10.1063/1.3514586
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional electron beam-plasma instabilities in the relativistic regime

Abstract: The interest in relativistic beam-plasma instabilities has been greatly rejuvenated over the past two decades by novel concepts in laboratory and space plasmas. Recent advances in this long-standing field are here reviewed from both theoretical and numerical points of view. The primary focus is on the two-dimensional spectrum of unstable electromagnetic waves growing within relativistic, unmagnetized, and uniform electron beam-plasma systems. Although the goal is to provide a unified picture of all instability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
300
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(314 citation statements)
references
References 237 publications
(334 reference statements)
13
300
1
Order By: Relevance
“…The kinetic oblique mode is indeed resposible for the peak in the electric field energy observed at ω e t ∼ 1000 in Figure 1(a) (red and blue lines), which produces a moderate increase in the fraction of beam energy transferred to the background electrons (orange line in Figure 1(a) at ω e t ∼ 1000). In this phase, the 2D structure of the longitudinal electric field in Figure 1 As expected, the increase in the transverse momentum dispersion has suppressed the modes having k ⊥ k , which are most sensitive to transverse temperature effects (e.g., Bret et al 2010b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The kinetic oblique mode is indeed resposible for the peak in the electric field energy observed at ω e t ∼ 1000 in Figure 1(a) (red and blue lines), which produces a moderate increase in the fraction of beam energy transferred to the background electrons (orange line in Figure 1(a) at ω e t ∼ 1000). In this phase, the 2D structure of the longitudinal electric field in Figure 1 As expected, the increase in the transverse momentum dispersion has suppressed the modes having k ⊥ k , which are most sensitive to transverse temperature effects (e.g., Bret et al 2010b).…”
Section: Resultsmentioning
confidence: 99%
“…Since the oblique mode is heating up the beam in the transverse direction (solid blue line in Figure 1(b)), the exponential growth at the reactive rate ω OBL will necessarily terminate, when the assumption of a cold beam required by the reactive approximation becomes invalid. It is well known that the system will transition from the reactive phase to the kinetic phase when the beam velocity dispersion ∆v b reaches (e.g., Fainberg et al 1970;Bret et al 2010b)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to standard geometry implicated in WI, recent theoretical studies of Bret (2009, Bret, Gremillet & Dieckman (2010) have also shown the importance of oblique modes.…”
Section: Introductionmentioning
confidence: 99%
“…7,11 The instability is driven by a thermal anisotropy of a single electron distribution rather than by counterstreaming electron beams 12 and is thus similar to the Weibel instability in its original form. [13][14][15][16][17] It is the result of the electron's slowdown by the ambipolar electrostatic field, which is sustained by the plasma density gradient of the rarefaction wave.…”
Section: Introductionmentioning
confidence: 99%